Survival outcomes and prognostic factors of primary small cell carcinoma of the esophagus - Miao, Huikai; Li, Rongzhen; Chen, Dongni; Hu, Jia; Chen, Youfang; Wen, Zhesheng (Journal of thoracic disease, 2021)
Primary small cell carcinoma of the esophagus (PSCCE) is a rare and aggressive malignancy. It has a poor survival rate, and there is no consensus as to a standard therapeutic modality. In this study, we aimed to investigate the prognostic factors and evaluate the outcomes of patients with PSCCE who had been treated with different therapeutic methods. We retrospectively evaluated 113 consecutive patients with PSCCE who received treatment at our center from 2003 to 2016. The primary endpoint was overall survival (OS). The Cox regression model was used to analyze the prognostic factors. The survival analysis was calculated using the Kaplan-Meier and log-rank methods. The 12- and 36-month OS rates of all 113 enrolled patients were 45% and 12%, respectively. A significantly prolonged OS rate was associated with lymph node stages N0-N1 (P=0.022), the Veterans' Administration Lung Study Group (VALSG) system limited-disease (LD) staging (P=0.040), and multimodality treatments (P=0.047). Patients with regional lymph node metastasis benefited more from surgery combined with chemotherapy than surgery or chemotherapy alone (P=0.046). Concerning chemotherapy, cisplatin plus etoposide was the regimen most commonly used to treat PSCCE patients (67.5%). An early lymph node stage, the VALSG LD staging, and multimodality treatments were identified as independent prognostic factors of PSCCE. Surgery combined with adjuvant chemotherapy was especially necessary for LD stage PSCCE patients with lymph node stages N1-3.